IDNLearn.com makes it easy to find the right answers to your questions. Join our interactive Q&A community and get reliable, detailed answers from experienced professionals across a variety of topics.
Sagot :
Sure, let's analyze Rahul's solution step by step to find out where he used the addition property of equality.
1. Original Equation:
[tex]\[ 2\left(x-\frac{1}{8}\right)-\frac{3}{5} x=\frac{55}{4} \][/tex]
Expanding the first term:
[tex]\[ 2x - 2\left(\frac{1}{8}\right) - \frac{3}{5} x=\frac{55}{4} \][/tex]
Simplifying:
[tex]\[ 2x - \frac{1}{4} - \frac{3}{5} x=\frac{55}{4} \][/tex]
2. Combining Like Terms:
[tex]\[ 2x - \frac{3}{5} x - \frac{1}{4}=\frac{55}{4} \][/tex]
Finding a common denominator for the terms involving [tex]\( x \)[/tex]:
[tex]\[ 2x = \frac{10}{5}x \implies \frac{10}{5}x - \frac{3}{5}x = \left(\frac{10-3}{5}\right)x = \frac{7}{5}x \][/tex]
Thus, we have:
[tex]\[ \frac{7}{5} x - \frac{1}{4}=\frac{55}{4} \][/tex]
3. Using the Addition Property of Equality:
To isolate the term with [tex]\( x \)[/tex], we add [tex]\( \frac{1}{4} \)[/tex] to both sides of the equation:
[tex]\[ \frac{7}{5} x - \frac{1}{4} + \frac{1}{4} = \frac{55}{4} + \frac{1}{4} \][/tex]
Simplifying:
[tex]\[ \frac{7}{5} x = \frac{55 + 1}{4} = \frac{56}{4} \][/tex]
4. Solving for [tex]\( x \)[/tex]:
[tex]\[ \frac{7}{5} x = \frac{56}{4} \implies x = \left(\frac{5}{7}\right) \left(\frac{56}{4}\right) \][/tex]
Simplifying further:
[tex]\[ x = \frac{5}{7} \times 14 = 10 \][/tex]
Therefore, Rahul used the addition property of equality in Step 3.
1. Original Equation:
[tex]\[ 2\left(x-\frac{1}{8}\right)-\frac{3}{5} x=\frac{55}{4} \][/tex]
Expanding the first term:
[tex]\[ 2x - 2\left(\frac{1}{8}\right) - \frac{3}{5} x=\frac{55}{4} \][/tex]
Simplifying:
[tex]\[ 2x - \frac{1}{4} - \frac{3}{5} x=\frac{55}{4} \][/tex]
2. Combining Like Terms:
[tex]\[ 2x - \frac{3}{5} x - \frac{1}{4}=\frac{55}{4} \][/tex]
Finding a common denominator for the terms involving [tex]\( x \)[/tex]:
[tex]\[ 2x = \frac{10}{5}x \implies \frac{10}{5}x - \frac{3}{5}x = \left(\frac{10-3}{5}\right)x = \frac{7}{5}x \][/tex]
Thus, we have:
[tex]\[ \frac{7}{5} x - \frac{1}{4}=\frac{55}{4} \][/tex]
3. Using the Addition Property of Equality:
To isolate the term with [tex]\( x \)[/tex], we add [tex]\( \frac{1}{4} \)[/tex] to both sides of the equation:
[tex]\[ \frac{7}{5} x - \frac{1}{4} + \frac{1}{4} = \frac{55}{4} + \frac{1}{4} \][/tex]
Simplifying:
[tex]\[ \frac{7}{5} x = \frac{55 + 1}{4} = \frac{56}{4} \][/tex]
4. Solving for [tex]\( x \)[/tex]:
[tex]\[ \frac{7}{5} x = \frac{56}{4} \implies x = \left(\frac{5}{7}\right) \left(\frac{56}{4}\right) \][/tex]
Simplifying further:
[tex]\[ x = \frac{5}{7} \times 14 = 10 \][/tex]
Therefore, Rahul used the addition property of equality in Step 3.
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Discover the answers you need at IDNLearn.com. Thanks for visiting, and come back soon for more valuable insights.